On the endogeneity of inflation targeting : preferences over inflation (2011)
Over the last quarter of a century, inflation targeting has become a popular monetary regime. Nevertheless, empirical evaluations of IT have shown contradictory results. Part of the reason is that IT in and of itself constitutes an endogenous decision and thus needs to be properly instrumented. In this paper, we show that preferences over inflation constitute a crucial determinant of IT: countries exhibiting greater inflation aversion are more likely to adopt IT.